2013
DOI: 10.1002/jor.22327
|View full text |Cite
|
Sign up to set email alerts
|

Sheep model for osteoporosis: Sustainability and biomechanical relevance of low turnover osteoporosis induced by hypothalamic–pituitary disconnection

Abstract: Hypothalamo-pituitary disconnection (HPD) leads to low bone turnover and osteoporosis in sheep. To determine the sustainability of bone loss and its biomechanical relevance, we studied HPD-sheep 24 months after surgery (HPD þ OVX-24) in comparison to untreated control (Control), ovariectomized sheep (OVX), and sheep 12 months after HPD (HPD þ OVX-12). We performed histomorphometric, HR-pQCT, and qBEI analyses, as well as biomechanical testing of all ewes studied. Twenty-four months after HPD, histomorphometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Our previous studies demonstrated that HPD induced a remarkable bone loss syndrome. The osteoporotic phenotype was caused by a profoundly low bone turnover, similar to senile osteoporotic patients . Trabecular bone loss was already evident 3 months after HPD and became increasingly prominent after 12 months.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous studies demonstrated that HPD induced a remarkable bone loss syndrome. The osteoporotic phenotype was caused by a profoundly low bone turnover, similar to senile osteoporotic patients . Trabecular bone loss was already evident 3 months after HPD and became increasingly prominent after 12 months.…”
Section: Discussionmentioning
confidence: 97%
“…Trabecular bone loss was already evident 3 months after HPD and became increasingly prominent after 12 months. Cortical thickness was diminished only after 12 months indicating that HPD might first affect the highly metabolically active trabecular bone . In the present study we analyzed the bone 8 months after HPD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, the apparent Young’s modulus E app and the bending strength σ max of each specimen were calculated using the equations and . The outer radius in the lateral direction α of the diaphyseal cortex and the second moment of area with reference to the anterior–posterior axis I y were defined from HR-pQCT slices as described previously [29]. …”
Section: Methodsmentioning
confidence: 99%
“…When the ovariectomy is combined with a disconnection of the hypothalamus-pituitary axis, osteoporosis occurs within a year with a lower bone mineral density also in the femoral trabecular and cortical bone [249]. This osteoporotic phenotype is sustained for at least two years [250]. Indeed, long bone defects can be investigated in this model [251].…”
Section: Sheepmentioning
confidence: 97%